Phenolic Compounds And Biological Activities Of Salvia Officinalis And Moringa Oleifera Leaves (International Journal of Environmental Sciences, 2025)
In this study, the phenolic content and biological activity of Salvia officinalis and Moringa oleifera leaves, were compared. Spectrophotometric methods are used to determine total phenolic content, total flavonoids, and 1,1-diphenyl-2-picrylhydrazyl (DPPH). The methanolic extracts' antibacterial activity against three bacterial strains (Escherichia coli, Staphylococcus aureus, and Salmonella enterica) and Candida albicans as yeast was tested using the agar-well diffusion method. High Performance Liquid Chromatography with Diode Array Detector (HPLC-DAD) was performed to determine the specific phenolic compounds by comparing the retention times of phenolic compounds in samples to 19 standard compounds. Salvia officinalis and Moringa oleifera had total phenolic contents of 166.574 and 96.066 mg GAE/g, total flavonoids of 127.573 and 139.591 mg GAE/g, and DPPH radical scavenging activity of 70.445 and 61.392, respectively. Salvia officinalis exhibited the highest antimicrobial action against Candida albicans, while antibacterial activity was equal in the two samples. The HPLC results revealed variances in phenolic content. Salvia officinalis exhibited high composition levels. The main compounds discovered in the Salvia officinalis and Moringa oleifera samples were rosmarinic acid and gallic acid, respectively. All results are compared to previous studies.